Search for lepton-flavor violating decays of the Higgs boson in the μτ and eτ final states in proton-proton collisions at √s=13 TeV; Physical Review D; Vol. 104, iss. 3 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Babaev A. A. Anton Anatoljevich; Okhotnikov V. V. Vitaly Vladimirovich (2021, 2021)
Title screen